Emerging Oil Consensus in the GCC Area; Explaining the Transition from Distributive Rent to Productive Rent - fariborz arghavani; Ali Dehghan; Arash Moradi (رهیافتهای سیاسی و بین المللی)
Extended AbstractIntroduction: The amazing economic development of the Persian Gulf Cooperation Council (GCC) countries in recent decades has led to the emergence of a new nucleus of capitalism in the Persian Gulf subsystem and the Middle East region. The kingdoms of the Persian Gulf have efficiently leveraged their rentier economies and the vast revenues from hydrocarbon resources to form a novel consensus on development, initially based on the utilization of hydrocarbon resources, and are now moving towards more diversified economic development. These developments created tremendous changes in the literature of the rentier state; In such a way that oil and the rentier state, previously considered obstacles to sustainable development, have become the main pillars of the movement towards development in these societies; In other words, the GCC countries are transitioning from allocative rent to productive rent in their path towards development. The purpose of this article is to explain the reasons for this change.Methods: This study employs an analytical-explanatory approach based on the analysis of micro and macro components and the conceptual framework of the development-oriented state. Utilizing both library and internet sources, it seeks to critically examine the influence of both international and domestic factors on the shift in development strategies, while addressing the shortcomings of the development-oriented state theory, particularly its lack of attention to international variables and their impact on domestic development processes.Findings: The findings of this research show that the occurrence of a series of political and economic factors such as a generational shift in leadership, the birth of development-oriented states, balancing foreign policy, using smart power and connecting to the global economy, have provided the basis for the formation of this new model of development. It has resulted in the formation of a new movement among the the GCC members, from the allocation rent to the productive one.Conclusion: In reality, for decades, the hydrocarbon resources of the Persian Gulf have served as the gateway for GCC countries to enter and participate in the global economy as energy suppliers. The instability of oil resources, the discovery of shale oil and instability in oil prices made these countries realize the necessity and importance of creating a diversified economic system. Along with these issues, the occurrence of developments at both internal and external levels pushed these countries towards a kind of consensus on the way of internal governance and foreign policy. The new generation of leaders came to power with mainly economic-oriented attitudes, and in search of ways to diversify the rentier economy of their countries, they started initiatives such as development perspective programs in all countries of the GCC. Under the influence of the new ideas of their leaders, these rentier governments, by using elements such as authoritarianism and following the authoritarian capitalist model, became productive and nurturing governments in the economic field, which today are the main implementers of development prospects with tools such as government branding and economic investments. At the same time, based on the new ideas of the new leaders regarding the importance of effective economic relations with the world and the pursuit of political-economic interests and opportunities simultaneously with the East and the West, they started to balance the foreign policy and have engaged in reciprocal relationships with partners like China and India in the East, as well as the United States and Europe in the West, while employing smart power strategies.